Prepositional clusters: investigative-oriented learning and English language teaching - Tan, Melinda Mui Leng (2000)
This thesis attempts to do three things. Firstly, it attempts to bring a new contribution to knowledge about fixed idiomatic expressions in English, by demonstrating that the overall meaning of such expressions need not always be conveyed by the presence of lexical words. Linguistic observation of natural and authentic language use has shown the existence of fixed idiomatic expressions consisting solely of grammatical words and possessing a particular overall meaning. Some of these expressions commonly found in everyday informal communication (written and spoken) are "this and/or that", "either or ", "round and round ", "ups and downs ", "on and off', etc. Secondly, the thesis will seek to illustrate through descriptive analysis that fixed expressions consisting solely of grammatical words can be called "units of meaning", using Sinclair's (1991a) position regarding form and meaning. Thus, a part of the thesis will be devoted to investigating the lexico-grammatical behaviour of such expressions. The analysis focuses solely on prepositional clusters, whose frequent usage in informal spoken and written communication makes them suitable for investigation. These prepositional clusters are composed of prepositions or words that can function as prepositions, and formed as a result of the common syntactic patterns in which they occur. Besides analysing cluster patterns that are composed solely of prepositions or words that can function as prepositions, other clusters which are composed of prepositions with adjectives/adverbs and nouns are included in the investigation, for purposes of comparison. Hence, the prepositional cluster patterns analysed in this study are: a) Prep+and+Prep (egs. ins and outs, up and down), b) Prep+Prep (egs. roundabout, upside down, inside out), c) Prep+Adv/Adj (egs. at most, at least), d) Adj/Adv+Prep (egs. excited about, worried about, angry about), e) Noun+ Prep (egs. Reason for, request for, excuse for) and f) Prep+Noun (egs. by mistake, by chance, by coincidence). In examining the lexico-grammatical behaviour of prepositional cluster patterns, I have applied linguistic principles from both Corpus Analysis and Cognitive Semantics. This approach, which combines two fields of linguistics, lends more depth to the analysis. While principles of Corpus Analysis are useful in determining common meaning usages and grammatical functions of prepositional clusters, principles of Cognitive Semantics are able to extend the interpretation of the meaning usages, with regard to metaphoricity. Consequently, I will utilise the principles in both fields to suggest a semantic representation of all the prepositional clusters analysed in the study, based on a superordinate classification rather than on a network one. The third and final part of the thesis seeks to apply the lexicogrammatical findings and the linguistic principles used in the study to pedagogy. More specifically, these findings, together with the linguistic principles of Corpus Analysis and Cognitive Semantics, have been utilised to construct activities which demonstrate a particular ELT methodology, which I have termed Investigative-Oriented Learning (IOL). IOL is meant to address the limitation of Communicative Teaching in developing investigative questioning in language learners. The aim of IOL thus is to empower learners with skills of Conscious Investigation which may enable them to be sensitive to patterns of language, and to their idiomatic and metaphorical meanings and grammatical functions. Prepositional clusters, which illustrate idiomaticity and metaphoricity in authentic language use, have been used as an example of language patterns to illustrate the methodology behind IOL.